Some Results of the Geophysical Investigation at the Late Eneolithic Settlement of Gordineşti II-Stînca goală, Edineț District, Republic of Moldova - Przybyła, Marcin M.; Sîrbu, Ghenadie; Rybicka, Małgorzata; Król, Dariusz; Sîrbu, Livia (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2017)
The aim of this article is to present the latest results of geophysical researches executed in April 2017 at the site Gordineşti II-Stînca goală in northern part of the Republic of Moldova. Based on very intriguing discoveries (i.e. remains of a dwelling, part of a clay platform and one pit) during the excavations carried out in 2016 and earlier, it was decided to investigate a larger area using non-invasive geophysical method. As a result, a few types of anomalies of different shapes were identified. It seems that these anomalies indicate the occurrence of remains of the dwellings as well as hypothetical main square between them in the centre of this fortified settlement.
Keywords: geophysical methods; non-invasive survey; Gordineşti group; Late Eneolithic; dwellings; ditch